2020
DOI: 10.1186/s13100-020-00212-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the Tc1/mariner superfamily reveals the unexplored diversity of pogo-like elements

Abstract: Background: Tc1/mariner transposons are widespread DNA transposable elements (TEs) that have made important contributions to the evolution of host genomic complexity in metazoans. However, the evolution and diversity of the Tc1/mariner superfamily remains poorly understood. Following recent developments in genome sequencing and the availability of a wealth of new genomes, Tc1/mariner TEs have been identified in many new taxa across the eukaryotic tree of life. To date, the majority of studies focussing on Tc1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 74 publications
(101 reference statements)
0
39
1
Order By: Relevance
“…We first applied our method to alignments between transposable elements drawn from the Tc1/mariner superfamily. We chose this TE family due to its wide phylogenetic distribution (Dupeyron et al, 2020), and because Tc1/mariner elements are well characterised as active TEs in C. elegans (Bessereau, 2006). We constructed a network in which each individual TE is a separate node and the weight of the connection between each node is determined by the sequence similarity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first applied our method to alignments between transposable elements drawn from the Tc1/mariner superfamily. We chose this TE family due to its wide phylogenetic distribution (Dupeyron et al, 2020), and because Tc1/mariner elements are well characterised as active TEs in C. elegans (Bessereau, 2006). We constructed a network in which each individual TE is a separate node and the weight of the connection between each node is determined by the sequence similarity.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, we selected one of these clusters, mc476, which was composed of two subfamilies annotated by our pipeline as Fot1 and Tc1 (Fig 2D). Fot1 TEs are most common in fungi, although some metazoan examples have been found (Dupeyron et al, 2020). The origin of this element in nematodes is thus unknown.…”
Section: Network Properties Illuminate Cryptic Sequence Features Of Tesmentioning
confidence: 99%
“…We included transposases from all DDE superfamilies in our analyses, updating the 17 superfamily framework of Yuan and Wessler (13), i.e. Tc1/mariner, Merlin, PIF/Harbinger, MULE (Mutator + Rehavkus), P, hAT, Kolobok, Novosib, Sola1, Sola2, Sola3, PiggyBac, CMC (CACTA, Mirage, Chapaev), Transib, Academ, Ginger, Zator , to include a total of 19 superfamilies, with the follow changes in line with recent research: (i) we split Pogo from Tc1/mariner to form its own distinct superfamily (59, 60) (ii); we grouped PIF/Harbinger with Spy as the superfamily PHIS (61); (iii) we included the newly described GingerRoot family (62).…”
Section: Methodsmentioning
confidence: 99%
“…We used the transposase amino acid sequences from Yuan and Wessler (13) for our database searches, except for MULE, Pogo, Tc1/mariner , and GingerRoot, where we used sequences from more recent analyses (53, 54, 62). We queried the NCBI nr database with BLASTp (63, 64), using a script to parse outputs, specifying table format output, including a column containing the subject sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Nine families are classically considered, and most of their phylogenetic relationships have been updated and are well defined: DD34E/Tc1 [25], DD34D/mariner [26], DD37D/maT [23], DD39D/GT [23], DD41D/VS [24], DD35E/TR [20], DD36E/IC [21], DD37E/TRT [27] and DD38E/IT [22]. However, until recently, studies have shown that many groups of ITm transposons carry the same DDE/D signatures but have different phylogenetic origins [28][29][30]. In particular, the DD34E/Gambol [31] and DDxD/pogo [30] transposons, which were designated as the Tc1/mariner superfamily, have been shown to form two separate superfamilies with good bootstrap support [30].…”
Section: Introductionmentioning
confidence: 99%